Risk Factor Profile and Quality of Life of Psoriasis Vulgaris - As'ad Naufal; Damayanti Damayanti; Etty Hary Kusumastuti; Afif Nurul Hidayati (Faculty of Medicine, Universitas Airlangga, 2021)
Background: Psoriasis is an autoimmune human skin disease. It is a chronic and recurrent lesion characterized by erythema patches with well-defined borders with rough, multi-layered, and transparent scales with a significant negative impact on patients' quality of life. Several risk factors for psoriasis can decrease patient’ quality of life. Purpose: To determine the risk factor profile and quality of life of psoriasis patients at the dermatology and venereology outpatient clinic at Dr. Soetomo General Academic Hospital Surabaya. Methods: This was a cross-sectional study involving new and control psoriasis patients. Their risk factors were evaluated using questionnaires, and their quality of life was measured using the DLQI questionnaires. The data was collected at the Dermatology and Venereology outpatient unit Dr. Soetomo General Academic Hospital Surabaya. Result: Of the 24 patients, the biggest risk factor for psoriasis patients was trauma/ Koebner phenomenon, as reported in 15 patients (62.5%), and 11 patients’ (45.8%) quality of life was affected. Conclusion: Trauma was the largest risk factor for psoriasis, and psoriasis has significantly affected patient’ quality of life.